2021
DOI: 10.1007/s13205-020-02599-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of COVID-19 spike protein in recognizing the ACE2 receptor of different mammalian species and its susceptibility to viral infection

Abstract: The pandemic COVID-19 was caused by a novel Coronavirus-2 (SARS-CoV-2) that infects humans through the binding of glycosylated SARS-CoV-2 spike 2 protein to the glycosylated ACE2 receptor. The spike 2 protein recognizes the N-terminal helices of the glycosylated metalloprotease domain in the human ACE2 receptor. To understand the susceptibility of animals for infection and transmission, we did sequence and structure-based molecular interaction analysis of 16 ACE2 receptors from different mammalian species with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 49 publications
0
13
0
2
Order By: Relevance
“…A previous study by Khan et al [ 31 ] showed that hACE2–RBD forms hydrogen bonds (H-bonds) with Glu30–Lys417, Glu35–Gln493, Glu38–Tyr449, Glu38–Gly496, Tyr41–Thr500, Tyr41–Thr500, Gln42–Gln498, Asn330–Thr500, Lys353–Gly502, Lys353–Gly496, and Lys353–Gln498, as well as a salt bridge between Glu30 and Lys417. Several other researchers also confirmed that the following residues were important in RBD attachment to hACE: Gly446, Tyr449, Leu455, Phe486, Gln493, Gly496, Gln498, Thr500, Asn501, and Gly502 [ 45 , 46 , 47 ]. Moreover, Phe486, Gln493, and Asn501 in RBD were the most important residues identified by the hACE2 receptor on infected human cells, which simplified the RBD–hACE2 interaction [ 31 , 48 ].…”
Section: Resultsmentioning
confidence: 92%
“…A previous study by Khan et al [ 31 ] showed that hACE2–RBD forms hydrogen bonds (H-bonds) with Glu30–Lys417, Glu35–Gln493, Glu38–Tyr449, Glu38–Gly496, Tyr41–Thr500, Tyr41–Thr500, Gln42–Gln498, Asn330–Thr500, Lys353–Gly502, Lys353–Gly496, and Lys353–Gln498, as well as a salt bridge between Glu30 and Lys417. Several other researchers also confirmed that the following residues were important in RBD attachment to hACE: Gly446, Tyr449, Leu455, Phe486, Gln493, Gly496, Gln498, Thr500, Asn501, and Gly502 [ 45 , 46 , 47 ]. Moreover, Phe486, Gln493, and Asn501 in RBD were the most important residues identified by the hACE2 receptor on infected human cells, which simplified the RBD–hACE2 interaction [ 31 , 48 ].…”
Section: Resultsmentioning
confidence: 92%
“…On the other hand, several studies have shown that the key amino acids from the RBD of SARS-CoV-2, Leu455, Phe486, Gln493, and Asn501 form stronger interactions with the host receptor, together with Lys417, thus causing SARS-CoV-2’s affinity for ACE2 to be 20 folds compared to SARS-CoV ( Lan et al, 2020 ; Yan et al, 2020 ). According to Koley et al (2021) , the interacting residues of RBD are Gln493, Tyr449, and Gly446. Khan et al (2021) , on the other hand, reported that hACE2-RBD forms hydrogen bonds between Glu30-Lys417, Glu35-Gln493, Glu38-Tyr449, Glu38-Gly496, Tyr41-Thr500, Tyr41-Thr500, Gln42-Gln498, Asn330-Thr500, Lys353-Gly502, Lys353-Gly496, and Lys353-Gln498, and also a salt bridge between amino acids Glu30 and Lys417.…”
Section: Resultsmentioning
confidence: 99%
“…According to the results of amino acid interactions, the bromelain-derived peptide was able to interact with the receptor-binding motif (RBM) of RBD by blocking unique residues designated as important in the binding of the human angiotensin-converting enzyme 2 (ACE2) cell receptor. The residues that are crucial for SARS-CoV-2 RBD binding to hACE2 are Gly446, Tyr449, Leu455, Phe486, Tyr491, Gln493, Gly496, Gln498, Thr500, Asn501, and Gly502 [ 66 , 67 , 68 , 69 ], as well as a salt bridge contributed by Lys417 [ 69 ]. The residues Phe486, Gln493, and Asn501 are the most important residues in the RBD identified by the hACE2 receptor on infected human cells because they facilitate RBD-hACE2 interaction [ 17 , 70 ].…”
Section: Resultsmentioning
confidence: 99%